SYSTEM METHODOLOGY OF DEVELOPMENT OF CORPORATE STRUCTURES OF HOTEL AND RESTAURANT BUSINESS - MIZJUK, BOHDAN; BARNA, MARTA; MELNYK, IRYNA; TRUT, OLHA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The aim of the article is to scientifically substantiate the theoretical and substantive characteristics of the system methodology for the management of corporate entities in the hotel and restaurant business as complex social systems. The article summarizes the fundamental basis for creating a concept of effective management of business units that are part of a complex corporate network of hotel and restaurant business. As a result of the research, three types of organizations engaged in certain types of business have been identified. They are considered from the standpoint of the functioning of complex social systems. It is shown that they are characterized by an active position of management, an integrated way of working, joint organization of strategic decision-making, the use of modeling apparatus, which together allows you to effectively implement relevant business processes. The simulation is proposed to be carried out on the basis of a special matrix that reflects the use of analytical and systems approaches for each type of organization, including hotel and restaurant business corporations.
Keywords: system methodology; development of corporate structures; interactive modeling; socio-cultural systems; business structures; hotel and restaurant corporations; matrix of development modeling; development concept; independent and interdependent variables; system and analytical approaches